Pragmatik Istifham (Makna yang Tersirat di Balik Pertanyaan) - Sagala, Rumadani (Universitas Islam Negeri Raden Intan Lampung, 2015)
As an integral part of ilmu Ma’ani, istifhamis an important topic in Balaghoh. Istifham, according to ‘ilmu Balaghah, has both ma’ana haqiqi (textual meaning) and ma’na mazazi (contextual meaning). Ma’ana haqiqi (textual meaning) is real meaning as a sentence denotes; while ma’ana mazazi is a contextual meaning or hidden meaning based on the context of sentence. This article will explore various kinds of istifhamwith contextual meanings mainly used in Qur’anic verses